PENGARUH MEDIA PEMBELAJARAN CARD SORT TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SEKOLAH DASAR NEGERI 1 KERU - Lale, Lale Tita Hardya Iswari; Nisa, Khairun; Sobri, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using the card sort media on the learning outcomes of Pancasila Education for fourth-grade students at State Elementary School 1 Keru. This research is a quantitative study with a quasi-experimental design using a pretest-posttest group design. Data collection techniques used are observation and tests. In this study, hypothesis testing was conducted using a simple t-test. The hypothesis test results showed that tcount 2.288 > ttable 2.018 with a significance value (2-tailed) of 0.027, which means 0.027 < 0.05. Therefore, H0 is rejected, and Ha is accepted. This indicates that the card sort media has a positive impact, and students achieve improved learning outcomes in Pancasila Education for fourth-grade students at State Elementary School 1 Keru.